Detrital zircon ages and trace element compositions of Permian–Triassic foreland basin strata of the Gondwanide orogen, Antarctica - Paulsen, Timothy; Deering, Chad; Sliwinski, Jakub; id_orcid:0 000-0003-3069-9978; Valencia, Victor; Bachmann, Olivier; Guillong, Marcel (Geosphere, 2017)
ISSN:1553-040X